Епігенетична мінливість статі квіток i створення на її основі однодомних форм конопель (Cannabis sativa L.) (до досліджень М.М. Гришка 1930-х рр.) - Maletsky, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
From positions of the modern theory of a heredity M.M. Gryshko's two classical works in 1930, devoted to creation of monoecious forms of a hemp from dioecious are analyzed. M.M. Gryshko used variability of flower type of hemp plants, caused by epigamic way of their determination. This type of variability in modern terminology designate as an epigenetic variability as it does not mention karyotypic changes in sexual chromosomes determining normally a flower sex in hemp. M.M. Gryshko has shown, that epigenetic variability of flower sexual status covers both primary and secondary characters of a sexual status in hemp. Epigenetically changed phenotypes of plants are inherited, and are successfully used in breeding of monoecious cultivars of hemp. M.M. Gryshko investigation is a first in world breeding practice experiment in which the variability of sexual characters of plants has been effectively used to create cultivars of simultaneously ripening hemp and then cultivars of monoecious hemp.